Conceptual components of medical and health discourse (using the concept of "Health" as an example) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article contains an overview of such concepts as “discourse”, “concept”, provides approaches to the definition of these definitions, and examines the conceptual components of discourse.